Behind the veil : Dalit women in panchayati raj - Dhaka, Sunita; Dhaka, Rajvir S. (Delhi : Abhijeet Publications, 2005)
Study with reference to Haryana, India.
Includes bibliographical references (p. [310]-327).
Keywords: Women -- Political activity -- India -- Haryana; Panchayat -- India -- Haryana; Local government -- India -- Haryana